Trans isomeric fatty acids in human milk and their role in infant health and development - Hatem, Okba; Kaçar, Ömer Furkan; Kaçar, Hüsna Kaya; Szentpéteri, József L.; Marosvölgyi, Tamás; Szabó, Éva (Frontiers in Nutrition, 2024)
It is well known that long chain polyunsaturated fatty acids (LCPUFAs) play an important role in neurodevelopment in the perinatal life. The most important source of these fatty acids is the diet, however, they can also be formed in the human body from their shorter chain precursors, the essential fatty acids. Since the WHO recommends exclusive breastfeeding for the first six months after birth, the exclusive source of these fatty acids for breastfed infants is human milk, which can be influenced by the mother's diet. Unsaturated fatty acids can have either cis or trans configuration double bond in their chain with distinct physiological effects. Cis isomeric unsaturated fatty acids have several beneficial effects, while trans isomers are mostly detrimental, because of their similar structure to saturated fatty acids. Trans fatty acids (TFAs) can be further subdivided into industrial (iTFA) and ruminant-derived trans fatty acids (rTFA). However, the physiological effects of these two TFA subgroups may differ. In adults, dietary intake of iTFA has been linked to atherosclerosis, insulin resistance, obesity, chronic inflammation, and increased development of certain cancers, among other diseases. However, iTFAs can have a negative impact on health not only in adulthood but in childhood too. Results from previous studies have shown that iTFAs have a significant negative effect on LCPUFA levels in the blood of newborns and infants. In addition, iTFAs can affect the growth and development of infants, and animal studies suggest that they might even have lasting negative effects later in life. Since the only source of TFAs in the human body is the diet, the TFA content of breast milk may determine the TFA supply of breastfed infants and thus affect the levels of LCPUFAs important for neurodevelopment and the health of infants. In this review, we aim to provide an overview of the TFA content in human milk available in the literature and their potential effects on infant health and development.